PP15 National Longitudinal Study of the Nutritional Habits of Adults with an Intellectual Disability - Analysis of Baseline Data. (10th September 2013) - Hayes, C B; Duffy, P; Burke, E; McCallion, P; McCarron, M
Abstract : Background: Adults with intellectual disability (ID) are known to have poor dietary habits and high rates of obesity. This population is thus at high risk for developing chronic conditions. Moreover, the process of de-institutionalisation is changing the way adults with ID are leading their lives and as this is a more recent phenomenon the effects of more independent living on dietary habits are largely unknown. This study provides a detailed account of the nutritional habits of older people (age 40+) with intellectual disability (ID) in Ireland. Methods: The data was collected as part of the first wave of the Intellectual Disability Supplement to the Irish Longitudinal Study on Ageing (IDS TILDA) on 753 persons with mild, moderate, severe and profound ID, to better understand their dietary habits. IDS-TILDA is a multi-wave national longitudinal study of older adults with ID. This analysis examined overall intake and variations in intake of food and beverages by age, gender, place of residence, level of ID and BMI. A multivariable analysis is currently being carried out. Results: Overall, carbohydrate, dairy and meat intake were broadly in keeping with recommended guidelines although milk intake was poor (38% reporting never or rarely drinking milk). Fruit intake was also poor, (25% reporting eating two or more portions per day), although 50% of all participants reported drinking fruit juice daily. One-third of participants reported eating more than one portion of vegetables per day. Age and gender had little effect on nutritional habits. Preliminary analysis showed that those with mild/moderate ID were more likely eat more bread (p < 0.001), eat less meat (p < 0.05), vegetables (p < 0.05) and dairy products (p < 0.05) than those with severe or profound ID. They were also more likely to be obese (p < 0.05) and much more likely to live independently or with family (p < 0.001) reflecting greater autonomy in their food choices. Conclusion: The study demonstrated important differences in dietary habits between those with mild /moderate ID who were much more likely to live independently or with family compared to those with severe/profound ID who were more likely to be in residential care. It highlighted a number of areas where the dietary habits of older adults with ID could be improved. As the data provides detailed analysis on the dietary habits of a national sample of older people with ID for the first time, it will inform the development of nutritional policy advice for this group of people and their carers.